SOCIAL AND ENVIRONMENTAL INFORMATION QUALITY ATTRIBUTES AND FINANCIAL PERFORMANCE OF LISTED MANUFACTURING COMPANIES IN NIGERIA. - Abdulsalam, Saka Tunde; Aliu, Olanrewaju Atanda (J-MACC : journal of management and accounting, 2025)
Abstract The perceptions of public concerning companies voluntary environmental and social information disclosure (ESID) is that the report is a mere public relation exercise which lack the information quality attributes required for making investment choice that can impact company’s financial performance. In view of this observation, this study investigated ESID quality of listed manufacturing companies in Nigeria (LMCN) based on the information quality framework of Global Reporting Initiative (GRI, G3) and examine the impact on operating cash flow (OCFL) for the period 2011-2018. Ex–Post Facto research design was used and data collected from annual reports and accounts of forty-seven (47) LMCN were analyzed based on the Random effect regression analysis. The regression result uncovered that quality of environmental and social information disclosure of LMCN substantively and clearly communicated their sustainability achievement, as a consequence sustainability conscious investors and other stakeholders were motivated to patronize and provide finance capital that improved companies OCFL. The study concluded that reasonable investment in social and environmental activities and sufficient disclosure that follow GRI quality guidelines would boost sales growth and as well attract finance capital that would improve company financial success indicated in OCFL. The study recommended that substantive investment in sustainability matter and positive disposition towards quality disclosure that reflects accountability and transparency would improve company reputation and attract investments fund of sustainability friendly investors which may improve company OCFL.